Numeracy and COVID-19: examining interrelationships between numeracy, health numeracy and behaviour. Issue 3 (16th March 2022) - Lau, Nathan T. T.; Wilkey, Eric D.; Soltanlou, Mojtaba; Lagacé Cusiac, Rebekka; Peters, Lien; Tremblay, Paul; Goffin, Celia; Alves, Isabella Starling; Ribner, Andrew David; Thompson, Clarissa; Van Hoof, Jo; Bahnmueller, Julia; et al.
Abstract : During the COVID-19 pandemic, people across the globe have been exposed to large amounts of statistical data. Previous studies have shown that individuals' mathematical understanding of health-related information affects their attitudes and behaviours. Here, we investigate the relation between (i) basic numeracy, (ii) COVID-19 health numeracy, and (iii) COVID-19 health-related attitudes and behaviours. An online survey measuring these three variables was distributed in Canada, the United States (US) and the United Kingdom (UK) ( n = 2032). In line with predictions, basic numeracy was positively related to COVID-19 health numeracy. However, predictions, neither basic numeracy nor COVID-19 health numeracy was related to COVID-19 health-related attitudes and behaviours (e.g. follow experts' recommendations on social distancing, wearing masks etc.). Multi-group analysis was used to investigate mean differences and differences in the strength of the correlation across countries. Results indicate there were no between-country differences in the correlations between the main constructs but there were between-country differences in latent means. Overall, results suggest that while basic numeracy is related to one's understanding of data about COVID-19, better numeracy alone is not enough to influence a population's health-related attitudes about disease severity and to increase the likelihood of following public health advice.